MENINGKATKAN HASIL BELAJAR DAN KREATIVITAS SISWA DENGAN MODEL PEMBELAJARAN PICTURE AND PICTURE PADA TEMA ENERGI DAN PERUBAHANNYA DI SDN 3 MAMBEN DAYA - Sri Wahyuni; Ida Aeni (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2022)
This study aims to determine the improvement of student learning outcomes and creativity by using the picture and picture learning model. This research is a classroom action research which consists of two cycles. The stages of research start from planning, implementing, observing, and reflecting. The research subjects were students of class IV SDN 03 Mamben Daya, totaling 13 people. Data collection techniques using tests, observations, and documentation. The data were analyzed using the percentage formula. The results showed that the picture and picture learning model was proven to improve student learning outcomes and creativity on the theme of energy and its changes. The increase in learning outcomes is seen from the percentage in the first cycle, which is 61%, and the second cycle is 88%. These data indicate that there has been an increase in student learning outcomes by 27%. The increase in creativity in this study was seen in the results of the creativity test in the first cycle of 43%, while the average percentage of students' creativity in the second cycle was 86%. The data shows that there has been an increase of 43%. The increase is related to the ability of students to provide answers based on the results of their thoughts after having discussions based on pictures related to energy materials and energy changes that have been observed. Students can provide an explanation of the material that has been studied according to their own understanding.